An efficient one-pot two catalyst system in the construction of 2-substituted benzimidazoles: synthesis of benzimidazo[1, 2-c]quinazolines. Issue 48 (19th October 2015) - Cimarelli, Cristina; Di Nicola, Matteo; Diomedi, Simone; Giovannini, Riccardo; Hamprecht, Dieter; Properzi, Roberta; Sorana, Federico; Marcantoni, Enrico
Abstract : The first CeCl3 ·7H2 O–CuI catalyzed one-pot procedure for the synthesis of functionalized 2-substituted benzimidazoles as a valuable strategy in both industry and academia. Abstract : The benzimidazole core is a common moiety in a large number of natural products and pharmacologically active small molecules. The synthesis of novel benzimidazole derivatives remains a main focus in medicinal research. In continuation of the efforts towards Ce(iii ) catalysts for organic transformations, we observed for the first time the activity of the iodide ion and copper cation in activating CeCl3 ·7H2 O in the selective formation of prototypical 2-substituted benzimidazoles. The one-pot CeCl3 ·7H2 O–CuI catalytic system procedure includes the cyclo-dehydrogenation of aniline Schiff's bases, generated in situ from the condensation of 1, 2-phenylenediamine and aldehydes, followed by the oxidation with iodine, which works as a hydrogen sponge. Mild reaction conditions, good to excellent yields, and clean reactions make the procedure a useful contribution to the synthesis of biologically active fused heterocycles containing benzimidazoquinazolines.